2002
DOI: 10.1006/mthe.2002.0813
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Gene Expression in Breast Cancer Cells in Vitro and Tumors in Vivo

Abstract: Gene therapy clinical trials for cancer frequently produce inconsistent results. Some of this variability could result from differences in transcriptional regulation that limit expression of therapeutic genes in specific cancers. Systemic liposomal delivery of a nonviral plasmid DNA showed efficacy in animal models for several cancers. However, we observed large differences in the levels of gene expression from a CMV promoter-enhancer between lung and breast cancers. To optimize gene expression in breast cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…36 We selected the lung fibroblast cell line as a representative normal cell line for comparison of promoter activity in this quick screening because lung is the major nonspecific targeted organ when a gene is delivered intravenously by cationic liposome. [14][15][16][17] On average, the topoIIa promoter possessed the highest level of activity in breast cancer cells and the lowest level of activity in normal or nonmalignant cell lines, suggesting that it has the highest degree of breast cancer specificity. The other promoters had either a lower level of activity in breast cancer cells (ceruloplasmin and transferrin receptor) or a higher level of activity in normal cells (B-myb).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…36 We selected the lung fibroblast cell line as a representative normal cell line for comparison of promoter activity in this quick screening because lung is the major nonspecific targeted organ when a gene is delivered intravenously by cationic liposome. [14][15][16][17] On average, the topoIIa promoter possessed the highest level of activity in breast cancer cells and the lowest level of activity in normal or nonmalignant cell lines, suggesting that it has the highest degree of breast cancer specificity. The other promoters had either a lower level of activity in breast cancer cells (ceruloplasmin and transferrin receptor) or a higher level of activity in normal cells (B-myb).…”
Section: Resultsmentioning
confidence: 99%
“…50 When the luciferase gene is delivered by liposome through tail vein injection in a mouse model, however, the principal sites of luciferase activity are the lung, heart and liver, and the luciferase activity in lung per microgram of tissue protein is one to two order higher than that in any other organs. [14][15][16][17] This fact could reflect that gene delivery efficiency depends not only on the interstitial retention, but also on the uptake of tissues, nuclear transport of DNA and tissuespecific promoter activity. 51 In this study, a similar biodistribution pattern was observed when the DOTAP: Chol-CMV-luc complex was injected through the tail vein of tumor-bearing mice (Figure 4d, upper panels).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, various types of promoters have been constructed, which shows higher levels of gene expression than CMV promoter. 52,53 In addition to the promoter, other transcriptional regulatory elements, such as intron and polyadenylation signal sequence, are also important. 54 The use of optimized transgene expression cassette would make lipoplexmediated gene therapy more efficient.…”
Section: Discussionmentioning
confidence: 99%